2020
DOI: 10.1111/crj.13307
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cognitive load on static balance in chronic obstructive pulmonary disease patients

Abstract: Patients with chronic obstructive pulmonary disease (COPD) have an increased risk of falling and hip fractures, compared to healthy subjects. 1 Beside the direct consequences of the fall, this increased risk has an indirect negative effect in COPD patients, likely due to increased stress, dyspnea, quality of life, and sociability, ultimately leading to reduced physical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Main COP variables used were area, velocity (in both anteroposterior (AP) and mediolateral (ML) directions), variability (AP and ML directions), and amplitude (AP and ML directions). Significant differences compared to healthy subjects were identified for each of these parameters, but results were heterogenous between studies [2729,32,33,35,36,3943,47,49]. The reported correlations between “static stability” and clinical factors are summarized in table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Main COP variables used were area, velocity (in both anteroposterior (AP) and mediolateral (ML) directions), variability (AP and ML directions), and amplitude (AP and ML directions). Significant differences compared to healthy subjects were identified for each of these parameters, but results were heterogenous between studies [2729,32,33,35,36,3943,47,49]. The reported correlations between “static stability” and clinical factors are summarized in table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies used force platform measurements including an important variety of centre of pressure (COP) parameters [27][28][29]32,33,35,36,[39][40][41][42][43]47,49,56,58,59,61,62]. Main COP variables used were area, velocity (in both anteroposterior (AP) and mediolateral (ML) directions), variability (AP and ML directions), and amplitude (AP and ML directions).…”
Section: [Insert Fig4]mentioning
confidence: 99%
“…Evidence on this component was sparse, and only few studies offered the opportunity to isolate information on cognitive influences and postural control of COPD patients. Cognitive tasks impair postural control performance in both COPD and healthy subjects [39,49,72]. Two studies [49,72] showed no supplementary effect of the cognitive task in COPD patients compared to controls while Morlino et al [39] found the opposite.…”
Section: Cognitive Influencesmentioning
confidence: 99%
“…Nineteen studies used force platform measurements including an important variety of centre of pressure (COP) parameters [27][28][29]32,33,35,36,[39][40][41][42][43]47,49,56,58,59,61,62]. Main COP variables used were area, velocity (in both anteroposterior (AP) and mediolateral (ML) directions), variability (AP and ML directions), and amplitude (AP and ML directions).…”
Section: [Insert Fig4]mentioning
confidence: 99%
See 1 more Smart Citation